Misdiagnoses in a Brazilian population with amyotrophic lateral sclerosis - Borghetti, Vinicius Stefani; Cintra, Vívian Pedigone; Ramos, Jean de Oliveira; Marques, Vanessa Daccach; Onofre, Patrícia Toscano; Santana, Victor Augusto Souza; Bezerra, Lua Flora Pereira; Tomaselli, Pedro José; Santos, André Cleriston José dos; Sobreira, Claudia Ferreira da Rosa; Marques Jr, Wilson (Arquivos de Neuro-Psiquiatria, 2022)
Background Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that affects the upper and lower motor neurons. The correct diagnosis at the onset of the disease is sometimes very difficult, due to the symptoms being very similar to those of other neurological syndromes.Objective This study aimed to analyze the initial manifestations, the specialty of the first physician visited due the initial complaint, the misdiagnoses, as well as the unnecessary surgical interventions in a new ALS Brazilian population.Methods The medical records of 173 patients with typical ALS were reviewed.Results The present study demonstrated that other symptoms, besides weakness, were very frequent as initial presentation of ALS, and orthopedics was the medical specialty most sought by patients at the onset of symptoms. Our frequency of misdiagnoses was 69.7%, and in 7.1% of them, an unnecessary surgical intervention was performed.Conclusions Amyotrophic lateral sclerosis presents a very large pool of signs and symptoms; therefore, there is an urgent need of increasing the disease awareness to other specialties due to the high frequency of misdiagnoses observed in clinical practice.
Keywords: Amyotrophic Lateral Sclerosis; Motor Neuron Disease; Diagnostic Errors; Unnecessary Procedures